Nursing of a patient with gastrointestinal bleeding treated with integrated traditional Chinese and western medicine treatment (1例消化道出血患者中西医联合用药护理体会) - XIE Yunong (解雨秾); LI Xueyuan (李学艳) (中西医结合护理)
This paper summarized the integrated traditional Chinese and western medicine treatment and nursing management of hypovolemic shock due to recurrent gastrointestinal bleeding in a patient with abnormal coagulation function. The symptomatic treatment was carried out based on the risk assessment, and comprehensive interventions such as airway management, complication prevention, psychological intervention, dietary guidance, medication care, Chinese herbal medicine intervention were implemented during the treatment. The gastrointestinal bleeding was controlled and no adverse reaction was observed during the treatment. (总结1例凝血功能异常患者因反复消化道出血继发低血容量性休克的中西医联合用药护理经验。通过科学评估, 积极对症治疗, 同时开展呼吸道管理、并发症防治、心理干预、饮食指导、用药指导、中药干预等护理措施, 患者消化道出血停止, 且治疗期间未出现其他不良反应, 症状得到改善并顺利出院。)